Analysis on Gene Expression Profile in Oncospheres and Early Stage Metacestodes from Echinococcus multilocularis. - Fuqiang Huang; Zhisheng Dang; Yutaka Suzuki; Terumi Horiuchi; Kinpei Yagi; Hirokazu Kouguchi; Takao Irie; Kyeongsoon Kim; Yuzaburo Oku (Public Library of Science (PLoS), 2016)
Alveolar echinococcosis is a worldwide zoonosis of great public health concern. Analysis of genome data for Echinococcus multilocularis has identified antigen families that can be used in diagnostic assays and vaccine development. However, little gene expression data is available for antigens of the egg and early larval stages. To address this information gap, we used a Next-Generation Sequencing approach to investigate three different stages (non-activated and activated oncospheres, and early stage metacestodes) of E. multilocularis (Nemuro strain). Transcriptome data analysis revealed that some diagnostic antigen gp50 isoforms and the antigen Eg95 family dominated in activated oncospheres, and the antigen B family dominated in early stage metacestodes. Furthermore, heat shock proteins and antigen II/3 are constantly expressed in the three stages. The expression pattern of various known antigens in E. multilocularis may give fundamental information for choosing candidate genes used in diagnosis and vaccine development.